Geology of the Monowai Rift Zone and Louisville Segment of the Tonga-Kermadec Arc: Regional Controls on Arc Magmatism and Hydrothermal Activity - Gray, Alexandra (Université d'Ottawa / University of Ottawa, 2022)
The Tonga-Kermadec arc in the SW Pacific comprises a chain of more than 90 volcanic complexes. A continuous 400-km long chain of volcanic activity along the central portion of the Tonga arc has become the focus of intensive research, extending previous studies that have focused on the southern Kermadec chain. Earlier interpretations of the Tonga arc have focused on a perceived lack of volcanism between ~21°S and ~27°S, adjacent to a bend in the trench caused by the collision of the subducting Louisville Seamount Chain (LSC). During swath mapping in 2002, it was revealed that this portion of the arc, including the Louisville and Monowai segments, is in fact one of the most volcanically active parts of the Tonga-Kermadec system. At this location, a combination of oblique convergence of the Pacific Plate and southward compression due to the collision of the LSC has resulted in left-lateral strike-slip faulting and rifting of the arc crust. This has produced a series of left-stepping arc transverse graben and horst structures that localize the voluminous volcanic activity. For this study, a new 1:250,000 scale geological map of the Louisville and Monowai segments has been constructed as a framework for a quantitative analysis of arc volcanism and the eruptive history of these segments. Two types of volcanoes dominate the arc front: deep caldera systems (collapse structures formed due to the evacuation of magma) within the arc rifts, and smaller volcanic cones between the rifts. The cone volcanoes tend to have small summit craters (<10 km3) whereas the large caldera volcanoes have major depressions of up to 50 km3. The cones are relatively undeformed, whereas the larger calderas are affected by multiple stages of collapse, asymmetric subsidence, and distortion caused by regional stresses. Surveys of the crater walls of the cone volcanoes show a predominance of volcaniclastic deposits, whereas the caldera volcanoes contain a high proportion of coherent lava flows. The caldera volcanoes also show a prevalence of basaltic melts compared to the more andesitic and dacitic cones. The largest caldera volcano is the Monowai volcanic complex (25°53’S) occupying a deep depression (Monowai Rift Graben) that crosses the arc front. The volcanic complex consists of a large caldera (12 km wide, 1600 m deep) and an adjacent stratovolcano (Monowai Cone) rising nearly to sea level. We suggest that the different types of volcanoes along the Louisville and Monowai segments reflect the influence of deep structures within the arc crust that have localized strikeslip and normal faulting.
Keywords: Arc volcanism; Caldera; Bathymetry; Seafloor Mapping